2016
DOI: 10.1590/0074-02760160311
|View full text |Cite
|
Sign up to set email alerts
|

A non-hepatotropic parasite infection increases mortality in the acetaminophen-induced acute liver failure murine model: possible roles for IL-5 and IL-6

Abstract: We evaluated the effects of a non-hepatotropic parasite infection (Taenia crassiceps) on the outcome of acetaminophen-induced acute liver failure in mice. Uninfected and T. crassiceps infected mice orally received either 300 mg/kg acetaminophen or water as vehicle (n = 5 per group). Survival analysis, hepatocyte necrosis, alanine aminotransferase (ALT) levels, CYP2E1 protein, interleukin (IL-) 5, and IL-6 were assessed for all groups. All infected mice died within 16 h after exposure to acetaminophen (Tc+APAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…IL-5 is a Th2 cytokine that has been confirmed to be associated with increased liver injury in hepatitis induced by lipopolysaccharide and concanavalin A. Only a few articles reported that APAP increases IL-5 expression in mouse liver [ 208 , 209 ]. Ginsenoside Rg3 reduces some inflammatory factors, including IL-5, and alleviates APAP hepatotoxicity [ 208 ].…”
Section: Role Of Inflammatory Mediators In Ailimentioning
confidence: 99%
See 1 more Smart Citation
“…IL-5 is a Th2 cytokine that has been confirmed to be associated with increased liver injury in hepatitis induced by lipopolysaccharide and concanavalin A. Only a few articles reported that APAP increases IL-5 expression in mouse liver [ 208 , 209 ]. Ginsenoside Rg3 reduces some inflammatory factors, including IL-5, and alleviates APAP hepatotoxicity [ 208 ].…”
Section: Role Of Inflammatory Mediators In Ailimentioning
confidence: 99%
“…Ginsenoside Rg3 reduces some inflammatory factors, including IL-5, and alleviates APAP hepatotoxicity [ 208 ]. De León-Nava et al do not find leukocytes infiltration in the liver parenchyma during APAP-induced ALF, probably because IL-5 causes liver injury in a leukocyte-independent manner or that IL-5 expression is an indirect consequence of liver injury and has no effect on pathology [ 209 ]. Researchers examined the expression of 40 cytokines in APAP-induced hepatotoxicity model mice and showed that APAP increases tenfold levels of IL-1α, IL-7, IL-17, CCL1, CCL3, CCL4, macrophage colony-stimulating factor (M-CSF) and CXCL9.…”
Section: Role Of Inflammatory Mediators In Ailimentioning
confidence: 99%